Adoção do planejamento estratégico pelos tribunais de contas brasileiros - Flávia de Araújo e Silva (2013)
The public sector organizations have undergone major reforms since the 1980s seeking greater efficiency and effectiveness. In Brazil, one of the government programs that are included in the list of these reforms is Promoex - Modernization Program of External Control System of Brazilian States, Federal District and Municipalities, focused on improving some points of weaknesses diagnosed in the Courts of Auditors, institutions responsible for external control of public sector. One goal of Promoex was the implementation of strategic planning in 100 % of the Courts. Thus, the aim of this study was to describe the adoptions of strategic planning and monitoring process by the Courts of Accounts in Brazil. The research methodology combined survey, documentary research, and participant observation in one of the Courts where the field study was conducted. The sample of this research consists of twenty-three Courts which responded to the questionnaire. As a result, it was found that this process is still new to many Courts and, for the vast majority, Promoex leveraged the implementation of strategic planning. Many of the Courts are experiencing a ripening stage of the process and not all best practices are being observed yet. The definition of performance indicators is one of the greatest difficulties of the monitoring system. There are several aspects of the isomorphism (Institutional Theory) in the process of formulating and defining the monitoring methodology. Regarding the description of the process, it was observed that: almost all organizations use the Balanced Scorecard for monitoring strategy, the deployment of the long-term plan is through annual plans, action plans, and projects; monitoring of projects, deadlines, actions, and goals is being done monthly, and, to a lesser extent, financial and qualitative indicators are also being monitored; meetings are held with the group of responsible for strategies and with the participation of senior management; it is being implemented a computerized system to assist monitoring process. Field study was conducted in one of the Courts to exemplify aspects of the monitoring process which showed evidence that the process is not fully institutionalized. Only four Courts adopt incentive systems, using variable remuneration associated with combined performance indicators (institutional, sectorial, and individual). Only four Courts are practicing accountability of results achieved with strategic planning to external stakeholders. Regarding the results achieved by Promoex, it was possible to verify some changes in the scenery diagnosed before the start of the Program: Courts are more integrated among themselves and with the cycle of government management; they began to adopt information technology strategic planning, investing in computerized solutions for practicing external control; they are also adopting more modern practices regarding personnel management, and they are adopting business process management. It was found that the Courts still have some hurdles to overcome putting the strategic planning and monitoring system operating effectively and thus to obtain the results achieved with strategic planning appropriately.